The implicit fear of power motive is associated with practice time in elite karateka and tennis players - Wegner, M.; Wieland, A.; Mempel, G. (International Journal of Sport and Exercise Psychology, 2017)
Competitions in sports like tennis or karate are characterized by a direct interaction of opponents with one athlete trying to dominate the other. The importance of the implicit power motive - the need to have impact on others - has previously been pointed out for elite sport performances in these interactive sports. We hypothesized that the implicit power motive is associated with practice intensity in elite tennis (Study 1) and karate (Study 2). In the two studies we assessed the implicit (hope and fear components) and explicit power motives of elite male athletes (N = 62) and found associations with athletes` current amount of practice hours and career highs in practice hours. Only the fear component of the implicit power motive was marginally positively associated with current and maximum amount of practice hours (Study 1, tennis) and significantly positively associated with additional practice time (Study 2, karate). The results suggested that elite athletes in interactive sports are motivated to practice in order not to lose (control) in competitions.